e-learning: recommendations for instructional designers and interface considering learning style - Santos, Givaldo Almeida; Schneider, Henrique Nou (EATIS'12 : proceedings of the 6th Euro American Conference on Telematics and Information Systems EATIS 2012 : 2012, Valencia, Spain, 2012)
To growing use of educational software in the educational practices among subjects geographically dispersed they are disturbing researchers of the area of Education, with relationship to the elements of the designs of interfaces and instructional that can interfere in the interactions among the authors enrolled in the process teaching-learning with the digital interfaces in net and to interfere in the quality of the usability of these adapts digital online. In this context, the present article intends to present a theoretical discussion about the guidelines and recommendations for the interface designs and instructional while elements that can affect the technical and pedagogic usability in the e-learning of learning digital enviroments.